Clinical outcomes of newborn screening for cystic fibrosis. Issue 1 (1st January 1999) - Waters, Donna L; Wilcken, Bridget; Irwig, Les; Van Asperen, Peter; Mellis, Craig; Simpson, Judy M; Brown, John; Gaskin, Kevin J
Abstract : AIM: To determine how early diagnosis of cystic fibrosis, using neonatal screening, affects long term clinical outcome. METHODS: Fifty seven children with cystic fibrosis born before neonatal screening was introduced (1978 to mid 1981) and a further 60 children born during the first three years of the programme (mid 1981 to 1984), were followed up to the age of 10. The cohorts were compared on measures of clinical outcome, including height, weight, lung function tests, chest x -ray picture and Shwachman score. RESULTS: Age and sex adjusted standard deviation scores (SDS) for height and weight were consistently higher in children screened for cystic fibrosis than in those born before screening. At 10 years of age, average differences in SDS between groups were 0.4 (95% CI −0.1, 0.8) for weight and 0.3 (95% CI −0.1, 0.7) for height. This translates to an average difference of about 2.7 cm in height and 1.7 kg in weight. Mean FEV1 and FVC (as percentage predicted) were significantly higher in the screened cohort at 5 and 10 years of age, with an average difference of 9.4% FEV1 (95% CI 0.8, 17.9) and 8.4% FVC (95% CI 1.8, 15.0) at 10 years. Chest x -ray scores were not different between the groups at any age, but by 10 years screened patients scored an average 5.3 (95% CI 1.2, 9.4) points higher on the Shwachman score. CONCLUSION: Although not a randomised trial, this long term observational study indicates that early treatment made possible by neonatal screening may be important in determining subsequent clinical outcomes for children with cystic fibrosis. For countries contemplating the introduction of neonatal screening for cystic fibrosis, its introduction to some areas in a cluster randomised design will permit validation of studies performed to date.